Respuesta :
Answer:
An equation of the line that passes through the points (-6, -2) and (-3,2) will be:
- [tex]y=\frac{4}{3}x+6[/tex]
Step-by-step explanation:
- Given the points (-6, -2) and (-3,2)
[tex]\mathrm{Slope\:between\:two\:points}:\quad \mathrm{Slope}=\frac{y_2-y_1}{x_2-x_1}[/tex]
[tex]\left(x_1,\:y_1\right)=\left(-6,\:-2\right),\:\left(x_2,\:y_2\right)=\left(-3,\:2\right)[/tex]
[tex]m=\frac{2-\left(-2\right)}{-3-\left(-6\right)}[/tex]
[tex]m=\frac{4}{3}[/tex]
As we know that the point-slope form
[tex]y-y_1=m\:\left(x-x_1\right)[/tex]
substituting the values [tex]m=\frac{4}{3}[/tex] and the point (-6, -2)
[tex]y-y_1=m\:\left(x-x_1\right)[/tex]
[tex]y-\left(-2\right)=\frac{4}{3}\:\left(x-\left(-6\right)\right)[/tex]
[tex]y+2=\frac{4}{3}\left(x-\left(-6\right)\right)[/tex]
[tex]y+2=\frac{4}{3}\left(x+6\right)[/tex]
Subtract 2 from both sides
[tex]y+2-2=\frac{4}{3}\left(x+6\right)-2[/tex]
[tex]y=\frac{4}{3}x+8-2[/tex]
[tex]y=\frac{4}{3}x+6[/tex]
Therefore, an equation of the line that passes through the points (-6, -2) and (-3,2) will be:
- [tex]y=\frac{4}{3}x+6[/tex]